Variability of polyphenolics extracts from different oil palm trees and evaluation of their effect on Coelaenomenodera lameensis larvae - Fagbohoun, Louis; COFFI, Alassan; GANFON, M. Y. HABIB; FAGLA MEDEGAN GOUSSANOU, SÈDAMI (My University, 2015)
Coelaenomenodera lameensis is an insect and the major pest of the oil palm. In case of strong attack, it causes up to 50% loss of production. Larval development of C. lameensis is more pronounced on sensitive palm tree Elaeis guineensis originating from La Mé, Yocoboué and Deli compared to tolerant palm trees Elaeis oleifera originating from Central American. The objective of this work is to study the variability content of polyphenols from different palm trees and their effect on the larvae of C. lameensis. To do this, the extracts from the leaflets of these palms were analyzed by HPLC and tested on larvae of the leaf miner. Considering the results, HPLC analysis has revealed additional peaks polyphenols characterizing trees palm Elaeis oleifera tolerant, the retention time of 22.9, 26.4 and 30.4 min. Furthermore, bio-essays conducted on the larvae of Coelaenomenodera lameensis showed differential mortality of these larvae following the origin, the time and the concentration of applied chemical extracts. Indeed, this result indicates that the molecules in the three characteristic peaks are probably potential polyphenols and are in charge of tolerance to C. lameensis
Keywords: Elaeis guineensis; Elaeis oleifera; leaf miner; HPLC; polyphenols